Increased cerebrospinal fluid levels of cytokines monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1β (MIP-1β) in patients with amyotrophic lateral sclerosis - Martínez, H.R.; Escamilla Ocañas, C.E.; Camara Lemarroy, Carlos Rodrigo; González Garza y Barrón, María Teresa; Moreno Cuevas, Jorge E.; García Sarreón, M.A. (2020)
Introduction: Neuroinflammation has recently been described in amyotrophic lateral sclerosis (ALS). However, the precise role of such proinflammatory cytokines as monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1β (MIP-1β) in ALS has not yet been determined. In this study, we determined cerebrospinal fluid (CSF) MCP-1 and MIP-1β levels and assessed their association with the duration and severity of ALS. Methods: Concentrations of MCP-1 and MIP-1β were determined in the CSF of 77 patients diagnosed with ALS and 13 controls. Cytokine levels were analysed in relation to ALS duration (< 12 months vs > 12 months) and severity (< 30 points vs > 30 points on the ALS Functional Rating Scale administered at hospital admission). Results: Higher CSF MIP-1β (10.68 pg/mL vs 4.69 pg/mL, P < .0001) and MCP-1 (234.89 pg/mL vs 160.95 pg/mL, P = .011) levels were found in the 77 patients with ALS compared to controls. There were no differences in levels of either cytokine in relation to disease duration or severity. However, we did observe a significant positive correlation between MIP-1β and MCP-1 in patients with ALS. Conclusions: The increase in MIP-1β and MCP-1 levels suggests that these cytokines may have a synergistic effect on ALS pathogenesis. However, in our cohort, no association was found with either the duration or the clinical severity of the disease.